Evaluating atomicity, and integrity of correct memory acquisition methods. (29th March 2016) - Gruhn, Michael; Freiling, Felix C.
Abstract: With increased use of forensic memory analysis, the soundness of memory acquisition becomes more important. We therefore present a black box analysis technique in which memory contents are constantly changed via our payload application with a traceable access pattern. This way, given the correctness of a memory acquisition procedure, we can evaluate its atomicity and one aspect of integrity as defined by Vömel and Freiling (2012). We evaluated our approach on several memory acquisition techniques represented by 12 memory acquisition tools using a Windows 7 64-bit operating system running on a i5-2400 with 2 GiB RAM. We found user-mode memory acquisition software (ProcDump, Windows Task Manager), which suspend the process during memory acquisition, to provide perfect atomicity and integrity for snapshots of process memory. Cold-boot attacks (memimage, msramdump), virtualization (VirtualBox) and emulation (QEMU) all deliver perfect atomicity and integrity of full physical system memory snapshots. Kernel level software acquisition tools (FTK Imager, DumpIt, win64dd, WinPmem) exhibit memory smear from concurrent system activity reducing their atomicity. There integrity is reduced by running within the imaged memory space, hence overwriting part of the memory contents to be acquired. The least amount of atomicity is exhibited by a DMA attack (inception using IEEE 1394). Further, even if DMA is performed completely in hardware, integrity violations with respect to the point in time of the acquisition let this method appear inferior to all other methods. Our evaluation methodology is generalizable to examine further memory acquisition procedures on other operating systems and platforms.